Strengthening Whistleblower Protection in Combating Corruption and Money Laundering: A Normative Legal Study - Adhalia Septia Saputri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
Law enforcement against corruption and money laundering is often constrained by closed criminal networks, complex financial transactions, and sophisticated asset concealment practices. In this context, whistleblowers serve a strategic function by providing internal information that may support crime detection, evidence gathering, and asset recovery. However, in Indonesia, whistleblowers remain vulnerable due to fragmented legal protection, unclear legal status, retaliation risks, counter-criminalization, and weak coordination among law enforcement institutions. This study aims to analyze the normative framework of whistleblower protection in corruption and money laundering cases, identify legal gaps and practical obstacles, and formulate an integrated model of legal protection. This research employs normative legal research using statutory, conceptual, jurisprudential, and comparative approaches. The analysis focuses on Indonesian regulations concerning witness and victim protection, the institutional role of the Witness and Victim Protection Agency (LPSK), and comparative whistleblower protection models in selected jurisdictions. The findings show that although Indonesia has established a general legal basis for witness and victim protection, the existing framework does not yet provide comprehensive, specific, and operational protection for whistleblowers. Key weaknesses include the absence of integrated reporting mechanisms, limited anti-retaliation guarantees, inadequate safeguards against criminalization, and low public trust in protection institutions. This study proposes regulatory strengthening, enhanced institutional coordination, non-criminalization guarantees, and the development of a secure and integrated reporting system. The study contributes to the development of a more responsive legal policy framework for strengthening whistleblower protection as a strategic instrument in combating corruption and money laundering.